Impact of Climate Change on the Level of Insurance Risk: A Perceptual Study in Nepal - Hakuduwal, Kishor; Pradhan, Gopal Man; Khwalapala, Sumitra (Nepal Journal of Multidisciplinary Research, 2025)
Background: Climate change is now emerging as a major concern to the insurance sector that are influencing their underwriting, pricing, and risk management policies, procedures, and systems. Natural calamities like floods, landslides, and earthquakes are aggravated by weather variations. Such incidents do not only cause massive economic losses, but also heighten the susceptibility of people and communities creating more workload on the insurance industry for effective risk management. The study aims to analyse the climate change and the level of insurance risk in Nepal. Methods: The research design used in the study is a descriptive and explanatory, where primary data was gathered using an online survey on 424 non-life-insured respondents of Kathmandu Valley with a 5-point Likert scale. It is analyzed using descriptive statistics, correlation, and multiple regression. The reliability and multicollinearity tests are used to assess the strength of the measurements. Results: The results indicate that extreme weather frequency and severity, geographical exposure, and internal risk management practices are strong predictors of financial vulnerabilities and claim volumes. However, existing climate rules are not yet directly affecting perceived risk levels, suggesting they may play a role due to poor enforcement, limited scope of control, and an imbalance between regulatory requirements and the actual climatic threat posed to insured individuals. Conclusion: The frequency and severity of extreme weather events, as the factors that significantly increase insurance risk in Nepal, raise the volumes of claims and financial liability. The geographical exposure also increases losses with the place-specific risks. Climate regulations do not have a direct impact, although the predominant element is physical risks. Novelty: This is a unique study to capture the under-researched context of Nepal. It employs a perceptual prism to examine the influence of climatic factors and geographical exposure in creating insurance risk in a developing economy.